Role of the gynaecologist in pre- and perimenopausal period - Pertyński, Tomasz; Stachowiak, Grzegorz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
The role of the gynaecologist in pre- and perimenopausal care cannot be overestimated. On the one hand she/he is often in Polish circumstances a first-contact doctor; on the other hand pre- and perimenopause are periods when care for the deteriorating female health status is extremely important. The gynaecologist’s task is complex, including some screening examinations, prophylactic actions (e.g. correction of BMI and propagation of a healthy lifestyle), good co-operation with other specialists and some concrete therapies with ultra low dose hormone therapy as an effective and safe tool for the treatment of many menopausal ailments as well as for the improvement of female quality of life.